THE RELATIONSHIP BETWEEN BOARD CHARACTERISTICS AND ENVIRONMENTAL DISCLOSURE: EVIDENCE FROM TURKISH LISTED COMPANIES - Akbas, Halil Emre (WALTER DE GRUYTER GMBH, 2016)
This study primarily aims to analyze the relationship between selected board characteristics and the extent of environmental disclosure in annual reports of Turkish companies, using a sample of 62 non-financial firms listed on the BIST-100 index at the end of 2011. The content analysis is used to measure the extent of environmental disclosure. Four board characteristics, namely board size, board independence, board gender diversity and audit committee independence, are considered as the independent variables that may have an impact on the extent of the environmental disclosures of Turkish companies. According to the results of the regression analysis, only board size has a statistically significant and positive relationship with the extent of environmental disclosure. This result implies that firms with larger boards disclose more environmental information than firms with smaller boards. On the other hand, the rest of the independent variables are found to be unrelated to the extent of environmental disclosure. The low degree of independence and gender diversity on the boards of the sample companies for the time period analyzed in the study could be one possible explanation for this result.
Keywords: Environmental disclosure; board characteristics; corporate governance; Turkish companies; CORPORATE SOCIAL-RESPONSIBILITY; VOLUNTARY DISCLOSURE; RISK DISCLOSURES; GOVERNANCE; DETERMINANTS; LEGITIMACY; ASSOCIATION; PERFORMANCE; MEDIA; FIRM; Business & Economics